A study of the fastest courses for professional triathletes competing in IRONMAN® triathlons - Mabliny Thuany; David Valero; Elias Villiger; Matheus Santos Sousa Fernandes; Pedro Forte; Katja Weiss; Pantelis T. Nikolaidis; Ivan Cuk; Beat Knechtle (Human Movement, 2024)
Purpose The IRONMAN® triathlon is an endurance multisport discipline of high popularity. Professional IRONMAN® triathletes need to qualify for the IRONMAN® World Championships and, therefore, would benefit from identifying the fastest race courses. Our purpose was to identify the fastest races held for professional IRONMAN® triathletes competing from 2002 to 2022.